(untitled) (INMR - Innovation & Management Review, 2023)
Purpose – The purpose of this paper is to assess the influence of innovation orientation dimensions on theperformance of manufacturing small- and medium-sized enterprises (SMEs) in Ghana.Design/methodology/approach – Probability sampling technique, particularly, simple randommethod, was used for this study. Approximately, 81% response rate was achieved from a total sample size of346. Furthermore, PLS-SEM technique was used to determine the relationships among the study variables.Findings – The result showed that market innovation significantly predicted SMEs’ performance.Conversely, non-significant positive nexus was established between process innovation and SMEs’performance as well as product innovation and SMEs’ performance.Practical implications – Based on the outcome, the stakeholders in the SME sector should aim atimproving their market, products and process innovations.Originality/value – Despite the importance attached to the employment of innovation in the SME sectorby scholars in the extant literature, studies involving dimensions of innovation orientation on SMEs’performance were not much seen in literature. This study enriched literature by determining the relationshipsbetween the innovation orientation dimensions and SMEs’ performance